2015
DOI: 10.1080/13657305.2015.1024348
|View full text |Cite
|
Sign up to set email alerts
|

The Economics ofKappaphycusSeaweed Cultivation in Developing Countries: A Comparative Analysis of Farming Systems

Abstract: & The farming of the red seaweed Kappaphycus alvarezii and related species as raw material for the hydrocolloid carrageenan rapidly spread from the Philippines in the late 1960s to Indonesia, Tanzania, and other tropical countries around the world. Although numerous studies have documented positive socioeconomic impacts for seaweed farming, factors such as diseases and distance to export markets have led to an uneven development of the industry. Using standard budgeting techniques, this study adapted productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 15 publications
3
87
0
3
Order By: Relevance
“…An economic analysis of seaweed cultivation around the tropical world (discussed in Section 10 of this chapter) has shown that in some countries, primarily Indonesia and the Philippines, Kappphycus farming is already a well-established industry, providing employment opportunities to thousands of coastal inhabitants who have reduced access to alternative livelihood sources (Valderrama et al, 2013(Valderrama et al, , 2015. However, this growth is already evidence that a large expansion in seaweed farming is viable both technically and economically in various conditions.…”
Section: Seaweed Production and Use In Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…An economic analysis of seaweed cultivation around the tropical world (discussed in Section 10 of this chapter) has shown that in some countries, primarily Indonesia and the Philippines, Kappphycus farming is already a well-established industry, providing employment opportunities to thousands of coastal inhabitants who have reduced access to alternative livelihood sources (Valderrama et al, 2013(Valderrama et al, , 2015. However, this growth is already evidence that a large expansion in seaweed farming is viable both technically and economically in various conditions.…”
Section: Seaweed Production and Use In Perspectivementioning
confidence: 99%
“…For example, Edwards and Watson (2011) conducted an economic analysis of Laminaria digitata farming in Ireland; Philippsen et al (2014) presented a cost analysis for ethanol produced from farmed seaweeds; SINTEF (2014) described a new bioeconomy for Norway based on the cultivation and processing of seaweeds; Lenstra et al (2011) and Van den Burg et al (2013) examined the economic feasibility of offshore seaweed production in the North Sea; Msuya (2011) considered the impact of seaweed farming on the socioeconomic status of coastal communities in Zanzibar; and Valderrama et al (2013Valderrama et al ( , 2015 analyzed the economics of farming for carrageenan in tropical conditions, as discussed in greater detail for the remainder of this section. The fact that seaweed farming continues and expands, in most, if not all, cases without distortions such as subsidies, attests to its profitability.…”
Section: Economic and Social Considerations Of Seaweed Farmingmentioning
confidence: 99%
“…Meanwhile, the problems are still faced by the fishermen related to the quality of seaweed, low price from buyer. Seaweed farming is particularly prone to bottom and bust cycles given the large number of small scale price-takers in the industry (Valderrama et al, 2015). Indeed, Valderrama mentions that seaweed farmers, traders and processors frequently make decisions based on speculations or misinformation.…”
Section: Characteristics Of Seaweed Farming In Serewe Baymentioning
confidence: 99%
“…(5) Infrastructure and facilities for the utilization of mariculture fishery resources, including a guidance and improving data and information for farmer's group. Valderrama et al (2015) suggest that minimum farm lines are still necessary to ensure adequate economics returns, and greater farming plots to improve the potential economy of under-performing systems. Finally, there should be colloboration work among cross sectors and different levels of institutions.…”
Section: Intervention Toward Seaweed Industry Development In West Nusmentioning
confidence: 99%
“…A floating system of 3x3 m rafts with a 45-day farming cycle for a total of 270 production days per year is being practised by the self-help groups (SHG) in the region (Valderrama et al, 2015). Considered as one among the most environmentally benign activity, it has considerable potential to augment the livelihoods of coastal dwellers in the country.…”
Section: Seaweed Farmingmentioning
confidence: 99%